(untitled) (Global Journal of Human-Social Science, 2016)
The discovery of coal in Maiganga village has attracted the location of coal mining industry in the area to mine an estimated proven cold reserve of 4.5 million tons. Coal mining has a significant impact on people lively hood and the environment, the environmental shock ranges from environmental degradation to destruction of wildlife and their habitat while on the other hand coal mining contribute to national gross domestic product. Data for the study were collected by means of geo-information techniques, questionnaire, oral interview and field observation. Generated data were analysed through digital image processing using IDRISI Taiga and Arc GIS Software. Descriptive statistics was used to present result obtained. Result revealed a significant conversion of land cover features to mining pits by coal mining activities which forces resident of Maiganga to migrate from their original settlement. Observation reveals that most of the mining pits were not reclaimed. The study also shows that mining activity has negatively affected the communities’ lively hood, because most of the respondents complained of inadequate basic infrastructure in the area such as roads, pipe borne water, hospital and other basic public amenities.